2004
DOI: 10.1086/422089
|View full text |Cite
|
Sign up to set email alerts
|

Hubble Space TelescopeSTIS Ultraviolet Spectral Evidence of Outflow in Extreme Narrow‐Line Seyfert 1 Galaxies. II. Modeling and Interpretation

Abstract: We present modeling to explore the conditions of the broad-line emitting gas in two extreme Narrow-line Seyfert 1 galaxies, using the observational results described in the first paper of this series. Photoionization modeling using Cloudy was conducted for the broad, blueshifted wind lines and the narrow, symmetric, rest-wavelength-centered disk lines separately. A broad range of physical conditions were explored for the wind component, and a figure of merit was used to quantitatively evaluate the simulation r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
233
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(242 citation statements)
references
References 83 publications
8
233
1
Order By: Relevance
“…Physically, this could indicate that the clouds are optically thick to electron scattering, with columns of > 10 24 cm −2 (consistent with the low ionisation broad lines forming in the disc: Collin-Souffrin et al 1980), or that the radiative acceleration only affects the front face of the cloud (Baskin, Laor & Stern 2014b). However, part of the Hβ line is clearly blueshifted (Figure 1), indicating that these objects could be so extreme that even part of the low ionisation lines (as well as the high ionisation lines such as CIV) come predominantly from a wind (see also Leighly & Moore 2004;Leighly 2004).…”
Section: Zeroth Order Estimates Of Mass and Mass Accretion Rate From mentioning
confidence: 71%
See 1 more Smart Citation
“…Physically, this could indicate that the clouds are optically thick to electron scattering, with columns of > 10 24 cm −2 (consistent with the low ionisation broad lines forming in the disc: Collin-Souffrin et al 1980), or that the radiative acceleration only affects the front face of the cloud (Baskin, Laor & Stern 2014b). However, part of the Hβ line is clearly blueshifted (Figure 1), indicating that these objects could be so extreme that even part of the low ionisation lines (as well as the high ionisation lines such as CIV) come predominantly from a wind (see also Leighly & Moore 2004;Leighly 2004).…”
Section: Zeroth Order Estimates Of Mass and Mass Accretion Rate From mentioning
confidence: 71%
“…Both are super-Eddington, but 1H0707 is more super-Eddington that PG1244, so has a stronger wind which explains its lack of narrow optical line emission by shielding the NLR, suppressing the narrow [OIII] lines compared to PG1244 (Leighly 2004). The combination of more highly superEddington flow leading to stronger mass loss, together with higher inclination angle means that the wind is more likely to be in the line of sight for 1H0707.…”
Section: The Difference Between Simple and Complex Nls1mentioning
confidence: 99%
“…Additionally, a density of 10 10.25 cm −3 was found from the study of UV intrinsic absorbers of two NLSy1 galaxies (Leighly 2004). Finally, from photoionization calculations, Różańska et al (2014) found the density of an intrinsic absorbing cloud in the bright quasar HS 1603 + 3820 to be of the order of n H ∼ 10 10 − 10 12 cm −3 .…”
Section: Role Of the Gas Densitymentioning
confidence: 89%
“…High-ionization lines (like C IV) are thought of as "wind" lines, because they can show a component with non-virialized motion, often interpreted in the context of a radiatively line driven wind. Some lines can have both a disk and wind component (see, e.g., Leighly 2004, and references therein). In order to drive a wind radiatively, the balance between the number of X-ray and UV photons is critical.…”
Section: Soft Ionizing Continua and Disk Windsmentioning
confidence: 99%